Does entrepreneurial risk-taking affect the business performance of micro-enterprises? Evidence from Skikda in Algeria - Ayoub Messikh (Naše gospodarstvo / Our Economy, 2022)
According to several previous studies, entrepreneurial risk-taking is an important aspect that can lead to prospective business opportunities, hence improving entrepreneurial outcomes such as enterprise performance. The main purpose of this paper is to examine the extent and degree of impact of entrepreneurial risk-taking (ERT) as one of the dimensions of entrepreneurial mindset on the performance of micro enterprises in Skikda, Algeria. Based on a self-administered survey questionnaire, data were collected from a random sample of 142 micro-enterprises in Skikda. The study adopted descriptive, correlation, and regression analyses to estimate the impact of entrepreneurial risk-taking. collected data were analyzed using the Statistical Package for Social Sciences (SPSS 22) programme. The findings demonstrate that entrepreneurial risk-taking significantly affects the performance of micro enterprises in Skikda. Of the total variance of the performance of micro enterprise's, 9.2% can be explained by the variability of entrepreneurial risk-taking. A small percentage is expected and can partly be explained by the presence of other factors that affect the performance of these enterprises as well as the negative effects of the COVID-19 pandemic on the process of economic activity and available business opportunities worldwide, especially these very small enterprises. However, the presence of this positive impact calls for a focus on raising the risk-taking spirit of existing and potential Algerian entrepreneurs, by holding conferences, forums and entrepreneurial programmes that enhance and support this characteristic of the entrepreneurial mindset.
Keywords: D81; L25; M13; 330; Risk taking; Entrepreneurship; Business performance; Micro enterprises; Skikda; Algeria